PROTECTING ROHINGYA REFUGEES IN ASEAN: THE CONTESTED HUMAN RIGHTS IN THE WORLD OF NA- TION-STATES - Zayzda, Nurul Azizah (Journal of Islamic Law Studies, 2018)
This paper departs from the concern that states’ policy towards refugees and asylum seekers around theworld has not necessarily encouraged a true meaning of refugee protection. Instead, the policy related to their situation has been founded on the ba- sis of states’ rights to accept asylum. In consequence, there have been always cases of refugees living in limbo, denied from protection or even deported to their home countries. The fact however needs to be not taken for granted, to be acknowledged as result of construction by wide range of actors; states, intergovernmental states, international non-governmental organizations, individuals, etc. This paper is partic- ularly interested in the ways that state through their actions- or inactions- establish a certain rhetoric about refugee rights. More specifically, this paper discusses the way ASEAN- referring to the regional organization and the individual states- shapes the rhetoric about refugee rights in their response to the Rohingya crisis. This paper collects and gather information regarding ASEAN meetings and policies as well as states’ initiatives and policies which directly or indirectly address the problems of Rohingya refugees. In order to understand how these policies form the way refugees rights is understood, this paper applies critical discourse analysis by revealing the direction to which the region and its individual states bring the overall discourse on refugee rights.